Determination of Renal Distribution of Zinc, Copper, Iron, and Platinum in Mouse Kidney Using LA-ICP-MS. (26th October 2021) - Stepka, Petr; Kratochvilova, Monika; Kuchynka, Michaela; Raudenska, Martina; Polanska, Hana Holcova; Vicar, Tomas; Vaculovic, Tomas; Vaculovicova, Marketa; Masarik, Michal
Abstract : The main dose-limiting side effect of cisplatin is nephrotoxicity. The utilization of cisplatin is an issue of balancing tumour toxicity versus platinum-induced nephrotoxicity. In this study, we focused on intraorgan distribution of common essential trace elements zinc, copper, and iron in healthy mouse kidneys and distribution of platinum after cisplatin treatment. Renal distribution in 12 nontreated Nu-Nu mice (males) was assessed by laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). Furthermore, 9 Nu-Nu mice were treated with cisplatin. The order of elements concentration in kidneys was as follows: Fe > Zn > Cu. All three metals showed the higher concentrations at the cortex and medulla (28.60, 3.35, and 93.83 μ g/g for Zn, Cu, and Fe, respectively) and lower concentration at the pelvis and the urinary tract (20.20, 1.93, and 62.48 μ g/g for Zn, Cu, and Fe, respectively). No statistically significant difference between cortex and medulla was observed for these elements. After platinum treatment, the concentration of platinum in kidneys was enhanced more than 60-times, p < 0.001 . Platinum significantly showed the highest accumulation in cortex (2.11 μ g/g) with a gradient distribution. Platinum was less accumulated in medulla and pelvis than in cortex, and the lowest accumulation occurred in the urinary tract (1.13 μ g/g). Image processing has been successfully utilized to colocalize metal distribution using LA-ICP-MS and histological samples images.